A STUDY OF ADJUSTMENT AND SELF EFFICACY OF UNDERGRADUATES STUDENTS - Kumari, Chanchal; Saxena, Deepshikha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Adjustment and Self-Efficacy are psychological concepts closely associated with the holistic development of student’s personality. Both serve as essential foundations for promoting mental health, fostering a positive outlook, and achieving success in life. The present study aims to analyse the relationship between Adjustment and Self-Efficacy among undergraduate students. For this purpose, a sample of 120 students (60 males and 60 females) was selected through a simple random sampling method from colleges affiliated with Bundelkhand University, located in Jhansi district of Uttar Pradesh. Adjustment was measured using the Adjustment Inventory for College Students developed by Dr. A.K.P. Sinha and Dr. R.P. Singh, while self-efficacy was assessed using the Self-Efficacy Scale developed by Dr. G.P. Bhatnagar and Dr. Rajkumari Bhatnagar. The data were analysed using statistical techniques such as Mean, Standard Deviation, T-test, and Product Moment Correlation. The findings indicated that female students had a better level of adjustment compared to male students, whereas males showed a higher level of self-efficacy than females. A positive and significant correlation was found between Adjustment and Self-Efficacy. Thus, it can be concluded that both Adjustment and Self-Efficacy contribute meaningfully to enhancing students’ mental well-being, confidence, and overall success in life.